A dimensão subjetiva da desigualdade social no ensino superior: um estudo sobre significações constituídas por estudantes bolsistas do Programa Universidade para Todos - PROUNI - Simões, Gabrielle Capinam da Silva (2021)
Social inequality is a complex phenomenon by which despite its economic dimension (unequal distribution of income and property, is also made of different aspects. Among them are those which are related to the presence of the subject in his composition and creates a specific dimension of phenomenon- a subjective dimension. It is a multifaceted problem that is present in many diverse areas, like the access to a special kind of education. A higher education on its part, is traditionally known for its excluding character, elitist, that is, occupied by students from the social privileged class. However, this scenario has been modified through public policies and institutional actions. There was an open process for those who historically do not have access to this place, like the young people of color who are from public schools and belong to the underprivileged class. This scenario, therefore, has been known by an expansion and increase access, giving way for a change in the social demographic profile of students of this teaching level. Even with this increase, as we analyze data from the economic and racial cutout, we realized that there is still a profound difference. The rich and white students still occupy a larger percentage of higher education when compared to the poor and young people of color. The objective of this research was to investigate a Subjective Dimension of social inequality in higher education: a study about the significance constituted by students with scholarship of a program called University for all. It was dedicated to the subjective dimension of social inequality, emphasizing on its expression on higher education, it is justified by the access to this level of education, especially, on the socioeconomic and racial cutout, which is still known by inequality, giving way for a reflection on this phenomenon. Knowing the significance that is contained in the words of the participants, allows us to increase our understanding of inequality, which after being studied by different areas of knowledge, still keeps its objective expressions. This research is based on a theorical perspective of socio-historical psychology. Inspired by the contribution of Fernando Gonzalez Rey, it was done through conversations on virtual platforms meetings, with two students in their last year of degree in psychology from a well-recognized institution in São Paulo, that receives a higher number of students from the upper middle and upper social classes, considered as a course meant for the elite. As an analysis procedure, we resorted to the core significance, a procedure proposed by Aguiar and Ozella, which help us in the appropriation of the subjects' perceptions and significance (signification) in face of reality. The set of significance analyzed, allows us to draw some conclusions: the analysis leads us to consider that the subjective dimension of social inequality, in its expression in higher education, is characterized by feelings of social humiliation and the presence of significance of effort and victory. In this way, the subjective dimension of social inequality reveals to us a field of antagonistic forces: that of living in a situation of those who suffer from social humiliation and, at the same time, experience a feeling of victory and achievement for the effort undertaken